Performance Study of a Superfine Cement–Bentonite-Based Emulsified Asphalt Composite Grout for Water-Bearing Sand Layers - Lei, Cao; Jingwei, Liang; Xiang, Wang; Maiyong, Jiang; Jinyou, Li; Chu, Jiang (Frontiers in Earth Science, 2022)
Grouting is an important and common method for fortifying water-bearing sand layers; however, this method is difficult to perform due to the poor groutability of these sand layers. This paper proposes superfine cement–bentonite-based emulsified asphalt composite grout (CACG) to infiltrate water-bearing sand layers. The grout uses superfine cement and bentonite as the base materials, while emulsified asphalt is added to achieve good pumpability, excellent fluidity, high stability and sufficient compressive strength. The effects of the composition and formulation on the performance of CACG is determined through a series of laboratory experiments, and the recommended optimal formulation of CACG is as follows: a water/superfine cement ratio of 1:1, a bentonite content of 6.5%, and an emulsified asphalt content of 20%. The effectiveness and economy of CACG is checked by a field test in which CACG is applied to the water-bearing sand layers of a river embankment. The results illustrate that CACG not only fulfills engineering requirements but is also cost effective.